2018
DOI: 10.1016/j.yfrne.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

TRPCing around the hypothalamus

Abstract: All of the canonical transient receptor potential channels (TRPC) with the exception of TRPC 2 are expressed in hypothalamic neurons and are involved in multiple homeostatic functions. Although the metabotropic glutamate receptors have been shown to be coupled to TRPC channel activation in cortical and sub-cortical brain regions, in the hypothalamus multiple amine and peptidergic G protein-coupled receptors (GPCRs) and growth factor/cytokine receptors are linked to activation of TRPC channels that are vital fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 119 publications
(195 reference statements)
5
33
0
Order By: Relevance
“…To elucidate the TRPC5 channel contribution to the postsynaptic activity of Kiss1 ARH neurons, we perfused TTX to block fast sodium channels and found that HC 070 significantly suppressed the senktide-induced inward current ( Figure 5E, F and H ). The I/V plot for the senktide-induced cation current exhibited the typical double-rectifying characteristics of TRPC5 channels with a reversal of −10 mV ( Figure 5G ) as we previously reported (Kelly Martin J. et al, 2018). These results indicate that TRPC5 channels also contribute to the synchronous activity of Stim1 kko neurons.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…To elucidate the TRPC5 channel contribution to the postsynaptic activity of Kiss1 ARH neurons, we perfused TTX to block fast sodium channels and found that HC 070 significantly suppressed the senktide-induced inward current ( Figure 5E, F and H ). The I/V plot for the senktide-induced cation current exhibited the typical double-rectifying characteristics of TRPC5 channels with a reversal of −10 mV ( Figure 5G ) as we previously reported (Kelly Martin J. et al, 2018). These results indicate that TRPC5 channels also contribute to the synchronous activity of Stim1 kko neurons.…”
Section: Resultssupporting
confidence: 82%
“…As expected, the selective PI3K inhibitor wortmannin (100 nM) robustly blocked the potentiation of the slow EPSP by insulin ( Figure 4A-E ). Next, we investigated a downstream effector of PI3K signaling based on our previous findings that TPRC5 channel protein is expressed in Kiss1 ARH neurons ( Figure 1C ) (Qiu J. et al, 2011) and is activated by the NKB agonist senktide (Kelly Martin J. et al, 2018). To measure the TRPC5 channels contribution to the slow EPSP, we used a ratio method in which a slow EPSP was generated with optogenetic stimulation (20 Hz, 10 s) of a Kiss1 Cre :ChR2 neuron and then tested again 10 min later after drug exposure (Qiu J. et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 NKB binds to TacR3 in neighboring Kiss1 ARH neurons to open TRPC5 channels to cause a robust depolarization (slow EPSP); coreleased dynorphin feeds back to bind to presynaptic κ-opioid receptors to limit the release of NKB to discrete bursts of activity and presumably postsynaptic TacR3 desensitization. 28,53 Thus, high-frequency autoexcitation of Kiss1 ARH neurons ipsilaterally is able to recruit Kiss1 ARH neurons bilaterally, which is dependent on NKB activation of TRPC5 channels to induce synchronization of this critical neural network that underlies the pulse generator activity in mammalian females. 27,28 The pulsatile LH secretion from NKB activation of Kiss1 ARH neurons was first shown in the goat through recording of multiunit activity (MUA) in close proximity of Kiss1 neurons simultaneously with measurements of LH release in the periphery.…”
Section: Kiss1 Arh Synchronous Neuronal Firing and Lh Releasementioning
confidence: 99%
“…3), which may be important for fertility, given that the TacR3 agonist senktide (and NKB) also excites Kiss1 ARH neurons through TRPC5 channels and NKB and TacR3 are critical for fertility. 53,68 Insulin, like leptin, affects neuropeptide expression in the hypothalamus and food intake. 69 Interestingly, insulin, similar to leptin, depolarizes and increases action potential firing in both POMC and Kiss1 ARH neurons.…”
Section: Role Of Kisspeptin Neurons In Feedingmentioning
confidence: 99%